Repertoire of human gut microbes. (May 2017) - Hugon, Perrine; Lagier, Jean-Christophe; Colson, Philippe; Bittar, Fadi; Raoult, Didier
Abstract: In 1675, Antoni Van Leeuwenhoeck was the first to observe several forms using an optical microscope that he named "animalcules", realizing later that these were microorganisms. The first classification of living organisms proposed by Ehrenberg in 1833 was based on what we could visualize. The failure of this kind of classification arises from viral culture, which preceded direct observations that were finally achieved during the 20th century by electron microscopy. The number of prokaryotic species is estimated at approximately 10 million, although only 1800 were known in 1980, and 14, 000 to date, thanks to the advent of 16S rRNA amplification and sequencing. This highlights our inability to access the entire diversity. Indeed, a large number of bacteria are only, known as Operational Taxonomic Units (OTUs) and detected as a result of metagenomics studies, revealing an unexplored world known as the "dark matter". Recently, the rebirth of bacterial culture through the example of culturomics has dramatically increased the human gut repertoire as well as the 18SrRNA sequencing allowed to largely extend the repertoire of Eukaryotes. Finally, filtration and co-culture on free-living protists associated with high-throughput culture elucidated a part of the megavirome. While the majority of studies currently performed on the human gut microbiota focus on bacterial diversity, it appears that several other prokaryotes (including archaea) and eukaryotic populations also inhabit this ecosystem; their detection depending exclusively on the tools used. Rational and comprehensive establishment of this ecosystem will allow the understanding of human health associated with gut microbiota and the potential to change this. Highlights: Bacterial communities, archaea, virus (including giant virus), fungi and parasites inhabits the human gut microbiota. Microbial culturomics using MALDI-TOF identification coupled with metagenomics allowed to extend the gut microbiota repertoire. Regarding the number of new bacteria described bacterial taxonomy must include genome sequencing as proposed by taxonogenomics.